HOW DO STUDENTS BEHAVE WITHIN THE FINAL EXAMS? - Halili, Halili (International Journal of Indonesian Education and Teaching (IJIET), 2020)
This study explores the attitudes and behaviors of Yogyakarta State University students within final exams as well as to analyze the factors that influence their attitudes and behaviors in taking those exams. This qualitative research employs a descriptive-analytic approach. The data are collected by observation on 740 students participating in the final exams and interviews with 20 people of them. Data gathering techniques used are observation, in-depth interview, and documentation. The result shows that the attitudes and behaviors of observed students within attending the final exams are categorized into the level of maximum-positive (65.7%), while 24.9% of them perform attitudes and behaviors that can be classified into the category of minimum-positive. On the other hand, the minority of them (8.4%) can be grouped into minimum-negative, and the rest (1%) is in the category of maximum-negative. Many factors are influencing the attitudes and behaviors of the maximum and minimum positive, namely: a) stances of preparation, b) spirituality and strong character, c) mental stand of â€˜nothing to lose'. Meanwhile, the factors influencing attitudes and behaviors of minimum and maximum negative categories are a) unpreparedness for exams, b) a sense of pseudo-collectivism and prejudice, and c) circumstance of opportunities.Â Corresponding author: Halili HaliliDOI: 10.24071/ijiet.2020.040208